Relationship between hyperlipidemia and the risk of death in aneurysm: a cohort study on patients of different ages, genders, and aneurysm locations - Ding, Dianzhu; Yang, Yongbin; Jiang, Guangwei; Peng, Yanhui (Frontiers in Physiology, 2023)
Aims: To assess the association of hyperlipidemia and the risk of death on the aneurysm population, focusing on age, gender and aneurysm location differences. Methods: All patients’ data of this retrospective cohort study were obtained from the Medical Information Mart for Intensive Care (MIMIC-III) database, and collected the baseline characteristics and laboratory parameters of all patients. COX regression model was established to explore the association of hyperlipidemia and the risk of death for patients with aneurysm. More importantly, subgroup analyses based on the age, gender, and aneurysm location differences were performed. Results: A total of 1,645 eligible patients were enrolled eventually in this study. These patients were divided into survival group (n=1,098) and death group (n=547) with a total mortality rate of 33.25% approximately. The result displayed that hyperlipidemia was associated with a decreased death risk of aneurysm patients. In addition, we also found that hyperlipidemia was associated with lower death risk of abdominal aortic aneurysm, thoracic aortic arch aneurysm among aneurysm patients who aged ≥60 years; hyperlipidemia was only a protective factor for the death risk of male patients diagnosed with abdominal aortic aneurysm. For female patients diagnosed with abdominal aortic aneurysm and thoracic aortic arch aneurysm, hyperlipidemia was associated with the decreased death risk. Conclusion: The relationship of hyperlipidemia, hypercholesterolemia and the risk of death for patients diagnosed with aneurysm was significantly associated with age, gender and aneurysm location.